Bile acids in combination with low pH induce oxidative stress and oxidative DNA damage: relevance to the pathogenesis of Barrett's oesophagus. Issue 6 (4th December 2006) - Dvorak, Katerina; Payne, Claire M; Chavarria, Melissa; Ramsey, Lois; Dvorakova, Barbora; Bernstein, Harris; Holubec, Hana; Sampliner, Richard E; Guy, Naihsuan; Condon, Amanda; Bernstein, Carol; Green, Sylvan B; et al.
Abstract : Background: Barrett's oesophagus is a premalignant condition associated with an increased risk for the development of oesophageal adenocarcinoma (ADCA). Previous studies indicated that oxidative damage contributes to the development of ADCA. Objective: To test the hypothesis that bile acids and gastric acid, two components of refluxate, can induce oxidative stress and oxidative DNA damage. Methods: Oxidative stress was evaluated by staining Barrett's oesophagus tissues with different degrees of dysplasia with 8-hydroxy-deoxyguanosine (8-OH-dG) antibody. The levels of 8-OH-dG were also evaluated ex vivo in Barrett's oesophagus tissues incubated for 10 min with control medium and medium acidified to pH 4 and supplemented with 0.5 mM bile acid cocktail. Furthermore, three oesophageal cell lines (Seg-1 cells, Barrett's oesophagus cells and HET-1A cells) were exposed to control media, media containing 0.1 mM bile acid cocktail, media acidified to pH 4, and media at pH 4 supplemented with 0.1 mM bile acid cocktail, and evaluated for induction of reactive oxygen species (ROS). Results: Immunohistochemical analysis showed that 8-OH-dG is formed mainly in the epithelial cells in dysplastic Barrett's oesophagus. Importantly, incubation of Barrett's oesophagus tissues with the combination of bile acid cocktail and acid leads to increased formation of 8-OH-dG. An increase in ROS in oesophageal cells was detected after exposure to pH 4 and bile acid cocktail. Conclusions: Oxidative stress and oxidative DNA damage can be induced in oesophageal tissues and cells by short exposures to bile acids and low pH. These alterations may underlie the development of Barrett's oesophagus and tumour progression.